Common mode voltage reduction in a three‐to‐five phase matrix converter fed induction motor drive. Issue 7 (1st June 2017) - Rahman, K.; Iqbal, Atif; Al‐Emadi, Nasser; Ben‐Brahim, Lazhar
Abstract : Multiphase power converters generate common mode voltage due to switching actions of the power switches. The resulting common mode current in multiphase motor drives flow through the bearing and shaft. Continuous flow of common mode current gradually weakens the performance of the drives. A space vector pulse width modulation (SVPWM) technique is developed to reduce Common mode voltage (CMV) in a three‐to‐five‐phase matrix converter‐based five‐phase induction motor drive system. The principle of CMV reduction lies in the selection of proper space vectors for implementation of SVPWM. The proposed technique achieves reduction in the CMV without affecting other performances, i.e. loss in output voltage, total harmonic distortion in the output voltages and currents. The common mode voltage is reduced by selecting a set of proper zero space vectors and placing them in a suitable position within a switching cycle. Using this approach, CMV is reduced by ∼30%. Simulation and experimental results are provided for a five‐phase induction motor drive fed using a three‐to‐five‐phase matrix converter.